PENGELOLAAN PROGRAM BANK SAMPAH DALAM MENINGKATKAN PEREKONOMIAN KELUARGA PADA BANK SAMPAH INDUK RUMAH HARUM DI KECAMATAN SUKMAJAYA - DEPOK - Faridah Faridah; Nurlina Nurlina (POLITEKNIK LP3I JAKARTA, 2023)
This study of the management of the Rumah Harum Main Waste- Bank focuses on the Fragrant House Main Waste Bank's waste management to enhance the economic well-being of families in the Sukmajaya subdistrict â€“ Depok area.The purpose of this research is to ascertain how Rumah Harum's waste bank program is managed in order to support the local families' economies.The qualitative research approach, which is described through elaboration or description based on the facts of the field, was used.The primary waste bank at Rumah Harum is responsible for managing waste-management by collecting it from the community and depositing it there as customers.The manager's passbook serves as the collection's savings account for the Sukmajaya Depok residents.The management of waste itself aims to transform waste into products that can be sold and to assist economically disadvantaged communities.The author draws the conclusion, based on the findings of the analysis, that the management of the waste bank is quite helpful and educates the public about how to choose waste and waste products that are collected and weighed into their savings when needed.However, the issue is that managers still require government assistance to properly manage waste, and the general public is still unaware of this.Keywords: Management, Â Waste Bank, Family Economy